Bus manufacturing: line balancing and optimization - Thirumal, Saravana Kumar (2021)
Bus production is a singular industry due to the product variety and customization usually required by clients. Buses are usually conceived based in a chassis where a frame is built, following the safety rules adopted by the sector. The external view can be similar, but some construction aspects and internal view are usually defined by the client, leading to a high customization. Thus, the bus can be manufactured in a common line, but the different configurations usually lead to a complex assembling process that needs to be carefully thought. Moreover, this kind of industry is permanently subjected to huge competitiveness and sustainable evaluation, which implies a rigorous cost planning and production, avoiding budget problems. This work was carried out in a bus manufacturer located in the Porto surroundings, which produces a large number of bus types for airports, tourism, urban or scholar purposes. The factory has three different production lines, being each one allocated to a different kind of bus manufactured. The lines needed an optimization and balancing improvement, thus, this study intended to make a contribution to this purpose.